Low variability at Hinf I locus of Major Histocompatibility Complex (MHC)- DQB gene in Indian Mithun (Bos frontalis) - D S Gonge; S K Niranjan; S K Mishra; R K Singh; S Kumar; R S Kataria (Journal of Livestock Biodiversity, 2025)
Genomic region corresponding to exon 2 of DQB gene was amplified from 79 Indian mithuns. Three primers were used (two forward and one reverse) to carry out Polymorphism studies. Amplified products of DQB genes were digested with HinfI restriction enzymes, which revealed a total of 2 restriction patterns in DQB. Nearly all the mithun population was found to be fixed for AA restriction pattern. PCR-RFLP results revealed very low variability at HinfI site in Bofr-DQB, contrary to PCR-RFLP studies of DQB gene in other bovines. Very low genetic diversity was observed at HinfI loci at exon 2 region of mithun DQB, indicating conserved recognition site of Hinf I.. Our study indicated that Hinf I enzyme may not be good enough for the typing of DQB alleles in mithun population, on other side tetracutters may a good choice for the genotyping of Bofr-DQB.